(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
An experimental study was designed to observe the hypocholesterolaemic effect of wheatgrass (Triticum aestivum) juice on experimentally induced hypercholesterolaemic rats, which was carried out in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka, from July, 2009 to June, 2010. A total number of 48 healthy adult male Long Evans rats (Norwegian strain), age ranging from 2-3 months, and weighing from 140-200 grams were used for the present study. 6 rats were taken in each group of total 8 groups treated differently with 1 control group. Rats of the first 5 groups were sacrificed at 29th day and their serum total cholesterol levels were measured. Rest of the rats were sacrificed at 57th day and their serum total cholesterol levels were measured. The mean serum concentration of total cholesterol of 10ml/kg grass juice fed normal rats was decreased by 11.64% than that of the laboratory diet fed control group (P<0.01). The total cholesterol of the group of rats treated with 10ml/kg grass juice and1% cholesterol diet were decreased by 36.59% than that of the hypercholesterolaemic control group (P<0.001). The mean total cholesterol of the hypercholesterolaemic rats treated with 10ml/kg grass juice for 28 days were decreased by 29.10%, and in hypercholesterolaemic rats treated with 20ml/kg grass juice for 28 days were decreased by 39.46% (P<0.001). The mean total cholesterol of the hypercholesterolaemic rats treated with 0.14mg/kg atorvastatin for 28 days were found to be decreased by 38.86% than that of hypercholesterolemic control group, which was statistically significant (P<0.001). DOI: http://dx.doi.org/10.3329/bjpp.v27i1-2.20070 Bangladesh J Physiol Pharmacol 2011; 27(1&2):21-27